Isolation and Characterization of Phosphate Solubilizing Bacteria from the Soils of Sikkim, India - Panda, Bhabatarini; Rahman, H.; Chatlod, L. R.; Panda, Jagabandhu (International Journal of Bio-resource and Stress Management, 2023)
The native population of phosphate solubilizing bacteria (PSB) was studied in the rhizosphere of maize, rice, ginger and large cardamom grown in different regions of Sikkim. A total of 26 best PSB were isolated based upon their solubilization on solid media from 104 rhizospheric samples collected from three agroclimatic zones. The population density of PSB showed large variations (2-36×106 cfu g-1) and biodiversity within the crop and place of sampling. Phosphate solubilization of these isolates varied from 46 to 160% and 30.2 to 203.7 mg L-1 in solid and liquid Pikovskaya’s medium, respectively. All the isolates were able to solubilize aluminium and iron phosphate significantly. Among the three phosphate sources all the isolates solubilized Ca3(PO4)2 to a greater extent than AlPO4 and FePO4 with AlPO4 exhibiting poor solubilization. The antibiotic resistance pattern showed large variations among the isolates and most of the isolates were resistant to ampicillin, methicillin and metronidazole. The highest PSB number and greatest variability were found in the rhizosphere of rice. Based on the morphological and biochemical analysis the isolates were clustered under the genera Bacillus, Pseudomonas, Micrococcus and Delftia. Among the four genera, Bacillus was the most predominant PSB found in all of soils tested